The Effect of Cold Swaging Deformation on the Microstructures and Mechanical Properties of a Novel Metastable β Type Ti–10Mo–6Zr–4Sn–3Nb Alloy for Biomedical Devices - Cheng, Jun; Wang, Hongchuan; Li, Jinshan; Gai, Jinyang; Ru, Jinming; Du, Zhaoxin; Fan, Jiangkun; Niu, Jinlong; Song, Hongjie; Yu, Zhentao (Frontiers in Materials, 2020)
In this work, the microstructures, texture evolution and mechanical properties of a newly designed metastable β type Ti-10Mo-6Zr-4Sn-3Nb (wt. %) alloy for biomedical devices subjected to cold swaging deformation at reductions of 15 %~75 % were investigated. With the increment in the reduction of swaging deformation, the grains are gradually broken and refined, and the stress-induced martensite (SIM) transformation occurs, resulting in the formation of α" phase. Moreover, the {112} <111> and {110} <112> textures turn into γ-fiber {111} <110> and α-fiber {112} <110> with the increment in the swaging reduction. Especially, the α-fiber texture firstly weakens and then strengthens during cold deformation. Under the combined effect of sub-structures, grain refinement and texture evolution, the strength of the alloy gradually enhances with the increment in the cold deformation reduction. The solution treated alloy bar shows superior cold workability in the process swaging. The plasticity remains at a moderate level under the effect of the initial grains that have not been completely broken at the beginning of the cold swaging deformation. The elastic modulus of the alloy shows a downward trend with the increasing in the reduction, which is related to the dislocation multiplication, grain refinement and grain orientation evolution during cold swaging deformation.